An octopus-mimic PEGylated peptide as a specific integrin αvβ3 inhibitor for preventing tumor progression. Issue 14 (23rd January 2020) - Shan, Xue; Zhang, Lei; Xu, Yurui; Sun, Lei; Guo, Leilei; Feng, Shujun; Ge, Haixiong; Gu, Tingting; Ning, Xinghai
Abstract : An integrin αvβ3 specific octopus mimicking peptide has been developed for enhancing tumor diagnosis and treatment. Abstract : We have developed a multivalent PEGylated RWrNR, named octopus-R, which exhibits good water solubility, biostability, biocompatibility and cancer targeting ability, endowing it with high anticancer potential. Octopus-R represents a promising theranostic agent and holds great potential for improving the management of malignant tumors.